3D Maskless Micropatterning for Regeneration of Highly Organized Tubular Tissues. Issue 3 (9th November 2017) - Ma, Chi; Qu, Tiejun; Chang, Bei; Jing, Yan; Feng, Jerry Q.; Liu, Xiaohua
Abstract: Micropatterning is a widely used powerful tool to create highly ordered microstructures on material surfaces. However, due to technical limitations, the integration of micropatterned microstructures into bioinspired 3D scaffolds to successfully regenerate well‐organized functional tissues is not achieved. In this work, a unique maskless micropatterning technology is reported to create 3D nanofibrous matrices with highly organized tubular architecture for tissue regeneration. This micropatterning method is a laser‐guided, noncontact, high‐precision, flexible computer programming of machining process that can create highly ordered tubules with the density ranged from 1000 to 60 000 mm −2 and the size varied from 300 nm to 30 µm in the bioinspired 3D matrix. The tubular architecture presents pivotal biophysical cues to control dental pulp stem cell alignment, migration, polarization, and differentiation. More importantly, when using this 3D tubular hierarchical matrix as a scaffold, this study successfully regenerates functional tubular dentin that has the same well‐organized microstructure as its natural counterpart. This 3D maskless micropattern approach represents a powerful avenue not only for the exploration of cell–material interactions in 3D, but also for the regeneration of functional tissues with well‐organized microstructures. Abstract : A unique maskless micropatterning technology is developed to create 3D nanofibrous matrices with highly organized tubular architecture for tissue regeneration. The tubular architecture presents crucial biophysical cues to dental pulp stem cell migration, polarization, and differentiation. When using this 3D tubular hierarchical matrix as a scaffold, functional tubular dentin is successfully regenerated with the same well‐organized microstructure as its natural counterpart.